Engagement in outdoor physical activity under ambient fine particulate matter pollution: A risk-benefit analysis - Ruopeng An; Hyojung Kang; Lianzhong Cao; Xiaoling Xiang (Elsevier, 2022)
Background: Outdoor physical activity (PA) brings important health benefits, but exposure to polluted air increases health risks. This study aimed to quantify the tradeoff of PA under fine particulate matter (PM2.5) air pollution by estimating the optimal PA duration under various pollution levels. Methods: A risk-benefit analysis was performed to estimate the optimal outdoor moderate-intensity PA (MPA) duration under varying PM2.5 concentrations. Results: An inverse nonlinear relationship was identified between optimal MPA duration and background PM2.5 concentration levels. When background PM2.5 concentration increased to 186 µg/m3, the optimal outdoor MPA duration decreased to 2.5 h/week, the minimum level recommended by current PA guidelines. When background PM2.5 concentration further increased to 235 µg/m3, the optimal outdoor MPA duration decreased to 1 h/week. The relationship between optimal MPA duration and background PM2.5 concentration levels was stronger when exercising at a location closer to a source of air pollution. Compared to the general adult population, adults aged 60 years and older had substantially steeper curves-the optimal outdoor MPA duration decreased to 2.5 h/week when background PM2.5 concentration reached 45 µg/m3. Conclusion: The health benefit of outdoor MPA by far outweighs the health risk of PM2.5 pollution for the global average urban background concentration (22 μg/m3). This modeling study examined a single type of air pollutant and suffered from measurement errors and estimation uncertainties. Future research should examine other air pollutants and indoor PA, incorporate short- and mid-term health effects of MPA and air pollution into the risk-benefit analysis, and provide estimates specific for high-risk subgroups.